Industry and Academic Partnership leads to Student Driven Success using an innovative Cloud Product in the classroom - O'Sullivan, Jill; Shahrier, Sayem (Journal of Systemics, Cybernetics and Informatics, 2018)
The relationships between Education/Training and Information Technologies at Farmingdale State College are accelerating, with the newest partnership involving the new CloudSuite Industrial Product, CSI, form Infor, USA, Inc. In this arrangement we have a dedicated Intern, Sayem Shahrier, a student at Farmingdale State College who assists with use of the CSI product in the classroom. According to this Intern, the implementation of the Infor CSI tool has been a great real life and hands-on experience. Students in the Education Alliance Program finally received a taste of how an ERP system works. Whether a company is big or small, it should be capable to manage and keep track of all their products and customers in real time. From local companies throughout Long Island all the way up to global mass markets have utilized the Infor CSI tool and have taken customer data to further maximize not only on profits but improve on operational excellence, customer intimacy, and the manufacturing process. Using this innovative tool and this partnership synergy, makes our students best prepared for industry entry and successes. This partnership brings together researchers and practitioners to support the bridging process between Education/Training and Information Technologies.
Keywords: dept.bis; peer-reviewed

A Study on Cloud Computing Adoption Within Small and Mid-Size Businesses (smbs) - Richardson, Anthony; Mate, Geoffrey (International Journal of Interdisciplinary Research, 2018)
A growing number of organizations have difficulty scaling-up their IT infrastructure to handle their growing needs and increased resource demands. Digital Technology Platforms (DTPs) have been identified by Gartner, Inc. as one of the top 10 strategic technology trends of 2017. While DTPs may be mainstream and easily adopted by large enterprise-sized organizations, there is an opportunity for such platforms within Small and Mid-Size Businesses (SMBs). The bottom line is that computing and server hardware is expensive for SMBs. Furthermore, it may be difficult for SMBs to assess and price the labor and resources needed for a company to have acceptable performance while controlling costs. The purpose of this paper is to examine how cloud computing technologies are adopted by SMBs and the respective drivers associated with costs and capability that may reduce costs for an organization. This paper explores how four variables – Robust Capability, Limited Capability, Cost Constraint, and Resource Abundance interact to impact the adoption of DTPs within SMBs. Adopters of DTPs are classified as Efficient, Proactive, Resistive, and Reactive. With respect to adoption efficacy, a model is proposed for assessing the capability and resource readiness as correlated to SMB adoption of DTPs. A study of 12 SMBs and the implementations of DTPs is presented and posited with the proposed adoption model. Due to the extensive investments required in procuring infrastructure services –adoption enablement is imperative for SMB-sized organizations to realize a return on investment. Implications are discussed.
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

How do humans interact with chatbots?: an analysis of transcripts - Park, Mina; Aiken, Milam; Salvador, Laura (International Journal of Management and Information Technology, 2018)
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/137-012-207-389-604 tex.type: [object Object]
Keywords: dept.bis; dept.mgt; peer-reviewed